1993
DOI: 10.2166/wst.1993.0429
|View full text |Cite
|
Sign up to set email alerts
|

Study on Statistical Characteristics of Nonpoint Pollutants Deposited in Urban Areas

Abstract: The objective of this study is to clarify the statistical characteristics of pollutants deposited in urban areas, taking account of stages (road surfaces, street inlets and streams) and land uses where they accumulated, from surveys over a period of 16 years in Kyoto City. The result of correlation analysis showed that there are intimate relationship between grain size and such pollutants as organic matter and nutrients. It showed the dependence of pollutants on grain size. After principal component analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Multivariate techniques including cluster analysis (CA), discriminant analysis (DA) and principal component analysis (PCA) have been applied to a variety of environmental applications including assessment of spatiotemporal change of rainwater quality (Wunderlin et al 2001;Vazquez et al 2003;Hamers et al 2003;Ouyang et al 2006), identification of rainfall runoff characteristics on different urban surfaces (Goonetillekea et al 2005;Yamada et al 1993;Huang et al 2007), and evaluation of the spatiotemporal patterns of land-based pollution on coastal areas (Zhou et al 2007a, b, c), etc. Obviously, previous studies provided valuable insights into the application of CA, DA and PCA techniques to environmental management and protection.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate techniques including cluster analysis (CA), discriminant analysis (DA) and principal component analysis (PCA) have been applied to a variety of environmental applications including assessment of spatiotemporal change of rainwater quality (Wunderlin et al 2001;Vazquez et al 2003;Hamers et al 2003;Ouyang et al 2006), identification of rainfall runoff characteristics on different urban surfaces (Goonetillekea et al 2005;Yamada et al 1993;Huang et al 2007), and evaluation of the spatiotemporal patterns of land-based pollution on coastal areas (Zhou et al 2007a, b, c), etc. Obviously, previous studies provided valuable insights into the application of CA, DA and PCA techniques to environmental management and protection.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of pollution prevention and control, indexed by the improvement of environmental quality or reduction of environmental damages (Downing 1984). The concentration of pollutants in the receiving water is shown to decrease in proportion to the progress of sewer construction (Yamada et al, 1993;Ning et al 2001).…”
Section: Development Of Tcc To Complete MCCmentioning
confidence: 99%
“…However, few studies on urban stormwater quality analysis by multivariate technique have been reported (Yamada et al 1993;Goonetilleke et al 2005). Characteristics of urban stormwater quality in Macau still remain poorly understood (Huang et al 2007).…”
mentioning
confidence: 99%